KEDUDUKAN HUKUM SURAT EDARAN MAHKAMAH AGUNG (SEMA) NOMOR 2 TAHUN 2023 TENTANG PERKAWINAN BEDA AGAMA - Delian Adlofeno (Unram Law Review, 2026)
Interfaith marriage has long been an issue in Indonesia, given the country's cultural diversity, particularly in the aspect of religion. Article 2, paragraph (1) of Law Number 1 of 1974 concerning Marriage stipulates that a marriage is valid if it is performed according to the laws of each party's respective religion and beliefs. Another provision, Law Number 23 of 2006 concerning Population Administration, in the Elucidation of Article 35 letter (a), states that "marriages determined by the court" refers to marriages between individuals of different religions. Based on these two provisions, interfaith marriage is fundamentally permitted under positive law. However, the Supreme Court Circular Letter (SEMA) Number 2 of 2023 regarding Guidelines for Judges in Adjudicating Applications for the Registration of Marriages between Persons of Different Religions and Beliefs essentially reinforces that judges and judicial bodies under the Supreme Court must not grant applications for the registration of interfaith marriages. In this context, SEMA Number 2 of 2023 contradicts the Marriage Law and the Population Administration Law, thereby creating a conflict of norms. This conflict of norms must be resolved based on the principle of lex superior derogat legi inferiori, which dictates that a lower-level regulation must not contradict a higher-level one. In this study, the author employs a statute approach and a conceptual approach to examine and resolve the issue of norm conflicts regarding interfaith marriage based on the prevailing laws in Indonesia.